Pengaruh Waktu Tinggal Kadar COD, BOD, TSS dan Amonia Pada Limbah Cair Industri Tekstil dengan Metode Constructed Wetland Menggunakan Tanaman Melati Air (Echinodorus Palaefolius) - Fathimah Azzahra, Dinda; Septa Hasannah, Cintiya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Textile waste has damaged the environment with various very high pollutants, such as high dissolved solids, COD, BOD, TSS and Ammonia. The high pollutant load in textile waste causes damage to aquatic ecosystems and affects human health if not managed properly. Constructed wetland is one of the efficient, effective and appropriate liquid waste treatment technologies because it uses a variety of vegetation. The study of the constructed wetland system using water jasmine plants (Echinodorus palaefolius) aims to reduce COD, BOD, TSS and Ammonia pollutants as an effect of detention time variations. Detention time includes 3,5,7 days. The results of the study showed that COD, BOD, TSS and Ammonia levels were affected by detention time. The efficiency of reducing COD levels on days 3, 5, and 7 was 58.38%, 54.30% and 55.45% respectively with concentrations of 397 mg/L, 430 mg/L and 425 mg/L. At BOD levels of 5.12%, 9.40% and 47.69% with concentrations of 111 mg/L, 106 mg/L and 61.2 mg/L. At TSS levels of 54.96%, 60.30% and 63.35% with concentrations of 59 mg/L, 52 mg/L and 48 mg/L. At Ammonia levels of 49.30%, 49.65% and 56.25% with concentrations of 1.46 mg/L, 1.45 mg/L and 1.26 mg/L. The results of textile wastewater quality standards are in accordance with the Minister of Environment Regulation No. 5 of 2014.